2006
DOI: 10.3748/wjg.v12.i4.636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic on isoniazid and rifampicin-induced hepatic injury in rats

Abstract: AIM: To evaluate the hepatoprotective effect of garlic on liver injury induced by isoniazid (INH) and rifampicin (RIF). METHODS:Wistar rats weighing 150-200 g were treated orally with 50 mg/kg of INH and RIF daily each for 28 d. For hepatoprotective studies, 0.25 g/kg per day of freshly prepared garlic homogenate was administered orally half an hour before the INH+RIF doses. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and bilirubin were estimated on d 0, 14, 21, and 28 in all the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 20 publications
11
52
0
1
Order By: Relevance
“…18 In another study by Pal et al it was seen that the treatment with (INH 50 mg/kg+ RIF 50 mg/kg) caused portal triaditis and liver necrosis. 19 In the present study administration of antitubercular drugs resulted in portal inflammation, ballooning degeneration, fatty change and necrosis in rat liver, which supports the findings of previous studies. 18,19 In the present study it was also found that there were no significant changes like portal inflammation, ballooning degeneration, fatty change and necrosis in groups treated with aqueous extract of tylophora asthmatica for 14 days.…”
Section: Discussionsupporting
confidence: 92%
“…18 In another study by Pal et al it was seen that the treatment with (INH 50 mg/kg+ RIF 50 mg/kg) caused portal triaditis and liver necrosis. 19 In the present study administration of antitubercular drugs resulted in portal inflammation, ballooning degeneration, fatty change and necrosis in rat liver, which supports the findings of previous studies. 18,19 In the present study it was also found that there were no significant changes like portal inflammation, ballooning degeneration, fatty change and necrosis in groups treated with aqueous extract of tylophora asthmatica for 14 days.…”
Section: Discussionsupporting
confidence: 92%
“…Bee pollen has been found to have some protective effect against carbon tetrachloride-induced toxicity [17] and malathioninduced toxicity [18]. Previous studies showed that antituberculosis drugs damaged the endogenous antioxidant system of the whole body [3][4][5][6][7] In our results, it is clearly reflected that supplementation of diet with bee pollen in animals has antioxidant and protective effect when given along with antituberculosis drugs (rifampicin as well as isoniazid). It is thus observed that bee pollen has strong potential to provide protection against antituberculosis drugs-induced toxicity in rats as evidenced by improved histological parameters and rebuilding of the antioxidant/oxidative status.…”
Section: Discussionsupporting
confidence: 59%
“…About 100 g of bee pollen contained about 396.4-411.1 kcal energy [16]. Rifampicin-and isoniazid-induced toxicity and oxidative stress relationship have been reported previously [3,4,7]. Mechanism of drug toxicity is through production of free radical and their capability to induce apoptosis by the production of ROS, lipid peroxidation, and cell membrane damage [5,6].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Suspension of isoniazid and rifampicin were separately prepared and given to rats in dose of 50 mg/kg each for 21 days via oral gavage tube (Pal et al, 2006).…”
Section: Isoniazid-and Rifampicin-induced Toxicitymentioning
confidence: 99%